Optimizing the charging protocol to address the self-discharge issues in rechargeable alkaline Zn-Co batteries. (15th February 2022) - Shang, Wenxu; Yu, Wentao; Xiao, Xu; Ma, Yanyi; Chen, Ziqi; Ni, Meng; Tan, Peng
Graphical abstract: Highlights: The self-discharge performance of a Zn-Co battery is investigated systematically. A new charging protocol is proposed to increase the amount of high valence state. The discharge capacity is improved from 220 to 290 mAh g −1 owing to activation. The capacity retention ratio after 10 h delay lifts from 72% to 90%. Abstract: Aqueous rechargeable Zn-Co batteries feature intrinsic safety and excellent electrochemical performance, and zinc metal is cheap with abundant reserves. However, a key issue, self-discharge, which may be fatal to the application, is always overlooked. Herein, the self-discharge performance is investigated systematically for the first time, and in-depth charge–discharge mechanisms are analyzed. Based on a free-standing Co3 O4 electrode, the insufficient utilization of the active material is found under a conventional galvanostatic charging process. Additionally, a dramatic attenuation in the open-circuit voltage is exhibited during the delay, leading to poor capacity retention. Through electrochemical tests and ex-situ characterization, the limited capacity and the severe self-discharge behavior are ascribed to the low amount and poor stability of the high valence state, respectively. Aiming at suppressing the self-discharge behavior, a novel charging protocol is proposed based on a new mechanism, which uses a time-controlling potentiostatic charging after the galvanostatic charging process. Using this strategy, the discharge capacity increases effectively by about 31.8% from 220 to 290 mA h g −1, and the capacity retention ratio after 10 h delay lifts from 72% to 90%. More importantly, the discharge capacity remains 100% after even 2500 cycles. This work puts forward a practical method for the operation of Zn-Co batteries, addresses the limiting issues for application, and greatly facilitates the improvement of this technology. Further, the results also inspire the research of other rechargeable Zn-based batteries.